Hydrogen titanate nanotubes for dye sensitized solar cells applications: Experimental and theoretical study - Pignanelli, Fernando (2018)
The existent research literature of Dye Sensitized Solar Cells (DSSC) is mainly focused on the dye but there are very few studies focused in the semiconductor. Here, we present the performance of hydrogen titanate nanotubes (HTNT), showing an enhancement of the solar cell efficiency from 5.95% to 7.63%, respect to anatase as photoelectrode. This enhancement could be explained in terms of open-circuit voltage, directly associated to the value of the HTNT band gap (Eg = 3.3 eV), the relative position of the edge conduction band; and the increase of the short-circuit current, directly associated to the enhancement of the specific area of the photoelectrode. All these characteristics are in very good concordance with our theoretical modelling of the system, based on First Principles calculations. We expect that this system could be further characterized, utilizing different dyes or absorbers, in order to evaluate the potential use of hydrogen titanate nanotubes for solar cell applications.